Flour babies - Fine, Anne.; Puffin Books (London : Puffin Books, 1992)
When his class of underachievers is assigned to spend three torturous weeks taking care of their own "babies" in the form of bags of flour, Simon makes amazing discoveries about himself while coming to terms with his long-absent father.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
6.2
5-8
7-9
Keywords: Babies -- Fiction; Parent and child -- Fiction; Schools -- Fiction; Infants -- Fiction; Parent and child -- Fiction; School stories